Semiotic Analysis of Lepo in Hewokloang Village - Yerika, Yohana; Nasa, Rikardus; Antonius M.K , Naro (Contemporary Education and Community Engagement (CECE), 2025)
Semiotics in traditional architecture is a symbolic language that conveys meaning through specific forms. These symbols are central to communicating meaning, allowing traditional buildings to reflect cultural values beyond their physical appearance. This study explores the semiotic meanings embedded in lepo, the traditional houses of the Hewokloang community. Using a qualitative approach, data were collected through interviews with indigenous stakeholders and direct observations at the study site. The findings reveal four main types of lepo in Hewokloang Village: Lepo Kirek, Lepo Hobat, Lepo Tana, and Lepo Musidole. Each lepo contains distinct symbolic elements expressed through its form, structure, and decorative details. These features are not merely aesthetic but are deeply rooted in the community's cultural values. Lepo Musidole features a carved figure of a man on its door leaf, symbolizing the individual who built the house. An umbrella-shaped roof ridge distinguishes Lepo Hobat, symbolizing its role as a place to prepare ceremonial materials. Meanwhile, Lepo Tana, constructed higher than the others, represents strength and authority. This study concludes that the symbolic elements of Hewokloang’s traditional houses are integral to understanding the community’s identity, beliefs, and social structure, demonstrating how architecture can serve as a cultural text that communicates meaning across generations.